2000
DOI: 10.1159/000013584
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>L</i>-Carnitine Supplementation on Cardiac Morbidity in Hemodialyzed Patients

Abstract: Cardiac diseases are well known among patients on maintenance hemodialysis (HD), and carnitine deficiency may be an important factor in cardiac morbidity. We studied the effects of low-dose L-carnitine treatment (500 mg/day) on chest symptoms (dyspnea on exertion, chest pain, palpitation), cardiac function, and left ventricular (LV) mass in 9 HD patients with reduced ejection fraction (EF). After 6 months of L-carnitine treatment, most patients had at least some improvement in chest symptoms, while LVEF was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 34 publications
2
31
2
Order By: Relevance
“…4 Inhibition of fatty acid metabolism in the carnitine-lacking myocardium could be a pathogenic mechanism in uremic cardiomyopathy, 35 and a risk factor for cardiomegaly in patients on maintenance HD. 34 In the present study, although no correlation was found between plasma free carnitine level and the echocardiographic parameters studied, there was a significant decrease in some of the cardiac diameters (LA, RV, LVED and LVES) and an increase in diastolic function (E/A ratio) after 2 months of oral L-carnitine supplementation. However, these parameters, except for E/A ratio, were still significantly different from those of the controls.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…4 Inhibition of fatty acid metabolism in the carnitine-lacking myocardium could be a pathogenic mechanism in uremic cardiomyopathy, 35 and a risk factor for cardiomegaly in patients on maintenance HD. 34 In the present study, although no correlation was found between plasma free carnitine level and the echocardiographic parameters studied, there was a significant decrease in some of the cardiac diameters (LA, RV, LVED and LVES) and an increase in diastolic function (E/A ratio) after 2 months of oral L-carnitine supplementation. However, these parameters, except for E/A ratio, were still significantly different from those of the controls.…”
Section: Discussioncontrasting
confidence: 75%
“…However, these parameters, except for E/A ratio, were still significantly different from those of the controls. Consistent with this finding, researchers 2,6,34,36,37 have reported a reduction of cardiomegaly, improvement of left ventricular function and performance, improvement of the metabolic and hemodynamic cardiac parameters, and improvement of cardiac complications (arrhythmia, reduced output, and low cardiothoracic ratio) in HD patients after L-carnitine treatment. However, cardiac thickness (RVAW, IVS, LVPW), left ventricular systolic function (FS and EF) and indices (MI, EDVI, ESVI) showed no significant changes after treatment and still these values continued to be significantly higher than controls.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…10 We previously reported that L-carnitine administration ameliorated myocardial fatty acid metabolism in patients undergoing HD. 11 There were also reports of improvement of cardiac dysfunction by L-carnitine supplementation, especially in patients with declined cardiac systolic function or with symptoms of heart failure; [12][13][14][15] however, when patients with normal myocardial function were studied, no benefit of carnitine was seen. 13,16 Left ventricular hypertrophy (LVH) is common and is an independent predictor of cardiac death in patients undergoing dialysis.…”
mentioning
confidence: 99%